Farming practices in smallholder pig production in Vietnam implications for food safety - Nguyen Thi Thu Huyen; Nguyen Thi Duong Nga; Pham Van Hung; Lapar, Ma. Lucila A.; Ninh Xuan Trung; Unger, Fred; Nguyen Van Pho (2018)
This paper aims to examine changes in pig farming practices that can improve food
safety of pig products in Vietnamese smallholder pig production. The study covered 615
pig households, which were analyzed using descriptive statistical analysis. Results show
that there is an increased trend of using own-produced piglets because farmers can apply
strict vaccine scheme for their piglets. The percentage of farmers applying vaccine in pig
production varies much depending on the type of diseases and location. Besides vaccine,
farmers follow good farming practices such as applying “all-in all-out” rule, isolating new
pigs, spraying disinfectant and cleaning pig barn regularly, and restricting visitors away
from the pig pens.
T-test results show that there are significant differences in some farming practices
between the two provinces considered in the study. In general, farmers in Hung Yen adopt
better production practices than farmers in Nghe An in terms of preventing pig diseases
and dealing with sick and dead pigs. However, some farmers are also engaged in risky
practices such as slaughtering sick pigs for home consumption, selling sick pigs to
slaughterhouses at lower price, and throwing away dead pigs instead of properly disposing
them. Increasing awareness of farmers about the importance of adopting good farming
practices through training and use of mass media could mitigate food safety and animal
health risks from pig production.
Keywords: Swine industry -- Vietnam; Food safety; Swine housing